2018
DOI: 10.1590/1807-3107bor-2018.vol32.0046
|View full text |Cite
|
Sign up to set email alerts
|

Do different strains of E. faecalis have the same behavior towards intracanal medications in in vitro research?

Abstract: The aim of this study was to evaluate the antimicrobial action of different endodontic pastes against Enterococcus faecalis ATCC 29212, isolated from the urinary tract, and compare the action with E. faecalis ATCC 4083, isolated from the root canal. For this purpose, dentin blocks were infected for 21 days with both bacteria at different time-intervals to ensure there would be no cross contamination. After this period, blocks were immersed in the test medications for 7 days, according to the following groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
7
0
4
Order By: Relevance
“…11 12 It has been shown that both medicaments appear to have promise as alternative for CH therapy in cases in which symptoms cannot be easily subsided. 13 14…”
Section: Introductionmentioning
confidence: 99%
“…11 12 It has been shown that both medicaments appear to have promise as alternative for CH therapy in cases in which symptoms cannot be easily subsided. 13 14…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do conhecimento do perfil multiespécie da infecção endodôntica, as avaliações dos biofilmes monoespécies de E. faecalis são fundamentais, pois esses microrganismos são mais resistentes à restrição de nutrientes na coexistência com outras espécies presentes nas infecções endodônticas (Gao, et al, 2016), mostrando maior sobrevida. A cepa de E. faecalis mais utilizada nos estudos in vitro é a ATCC 29212, com origem no trato geniturinário (Kangarlou, et al, 2016;Collares, et al, 2017;Cheng, et al, 2017;Swimberghe, et al, 2018), no entanto, o uso de cepas isoladas do canal radicular é recomendado, já que diferentes cepas da mesma espécie podem diferir devido a características adquiridas (Wang, et al, 2014;Barros, et al, 2014;Zancan, et al, 2018). Diante disso, optou-se pela inclusão de uma cepa isolada de canais radiculares necrosados (ATCC 4083) (Zancan, et al, 2018;Oda, et al, 2019).…”
Section: Discussionunclassified
“…A cepa de E. faecalis mais utilizada nos estudos in vitro é a ATCC 29212, com origem no trato geniturinário (Kangarlou, et al, 2016;Collares, et al, 2017;Cheng, et al, 2017;Swimberghe, et al, 2018), no entanto, o uso de cepas isoladas do canal radicular é recomendado, já que diferentes cepas da mesma espécie podem diferir devido a características adquiridas (Wang, et al, 2014;Barros, et al, 2014;Zancan, et al, 2018). Diante disso, optou-se pela inclusão de uma cepa isolada de canais radiculares necrosados (ATCC 4083) (Zancan, et al, 2018;Oda, et al, 2019). Nesse estudo, não houve diferença significante com os resultados encontrados comparando-se as cepas.…”
Section: Discussionunclassified
“…The viability of the remaining microorganisms after instrumentation and disinfection of root canals contributes significantly to endodontic treatment failure [1]. In the absence of clinical evidence that intracanal medicaments are sufficiently effective against persistent bacterial infections, there is a need for further investigation of new medicaments for use in periradicular conditions [2].…”
Section: Discussionmentioning
confidence: 99%
“…The success of endodontic treatment is related to the elimination of microorganisms from the root canal system [1,2]. Persistent infection after endodontic treatment, resulting from remnants of bacteria in root canal systems in areas of anatomical complexity and difficult access, continues to present a challenge in endodontics [1]. Thus, recurrent periapical infections are mainly associated with Enterococcus faecalis [2].…”
Section: Introductionmentioning
confidence: 99%